Peranan Cendawan Mikoriza Arbuskula Terhadap Pertumbuhan Leucaena leucocephala dalam Kondisi Cekaman Garam - Delvian Delvian (Jurnal Agrista, 2007)
Rule of Arbuscule Mycorrhiza Fungi on Growth of Leucaena leucocephala Under Salt StressABSTRACT. Symbiosis Arbuscule Mycorrhiza Fungi (AMF) and plant were not only improving growth and nutrition absorption, but also crop tolerance salinity. Increasing of tolerance to salinity following colonization of AMF promising due to phosphate absorption more efficient. Phosphate absorption of mycorrhizal plant mount equal to 115% compared to non-mycorrhizal plant. This issue will improve growth of crop and decrease influence of toxic ions. Mycorrhizae also can lessen forming of proline equal to 64.47% one of the way of osmotic adjustment of non mycorrhizal plant to increase tolerance. Despitefully accumulate sodium in mucorrhizal plant lower than non mycorrhizal, were degradation of sodium accumulation equal to 61.58%.